Constructing a model of effective information dissemination in a crisis. Information dissemination, Crisis, Crises, Tuberculosis, Dissemination of information, Meta-ethnographic analysis, Social marketing - Fiona Duggan; Linda Banwell (Information Research: An International Electronic Journal)
A model of effective information dissemination in a crisis was developed from a Ph.D. study of information dissemination during a suspected TB outbreak. The research aimed to characterise and evaluate the dissemination of information to the community during the incident. A qualitative systematic review of the research literature identified twenty relevant studies. Meta-ethnographic analysis of these studies highlighted the key factors in effective dissemination. Consideration of these factors in relation to dissemination theory provided the links between the key factors. When the resulting model was applied to the specific circumstances of the incident two barriers to effective information dissemination were identified. Incorporating these barriers into the original model enabled the construction of a model of effective information dissemination in a crisis. The implications of this model for information professionals include incorporating social marketing as a core element of education and training and adopting multi-method dissemination strategies.